Student Participation of The Teaching Campus Program in an Effort to Increase Children's Interest in Reading Through The Reading Literacy Movement at SDN 2 Pujokerto - Defri Ahmad Muhklis; Elizar Elizar; Berta Apriza (Green Publisher Indonesia, 2024)
This research aims to analyze student participation in the Teaching Campus program in an effort to increase children's interest in reading through the reading literacy movement at SDN 2 Pujokerto. The Class 4 Teaching Campus program is a continuation of the previous classes of the Teaching Campus program, namely classes 1, 2 and 3. The background to this research arises from the phenomenon of declining interest in reading among elementary school children caused by technological developments and lack of access to interesting and age-appropriate reading books. The Teaching Campus Program is one of the initiatives launched by the government in order to improve the quality of education in remote, outermost and disadvantaged areas (3T), especially in terms of children's interest in reading. This research uses qualitative research methods with descriptive analysis and direct observation results in the field. The participants in this research included students participating in the Teaching Campus program, teachers at SDN 2 Pujokerto. The results of the research show that student participation has significantly increased students' interest in reading at SDN 2 Pujokerto. This is demonstrated through creative activities carried out such as the Reading Corner Literacy Activity, visiting the library and making school posters. In addition, there is increased access to reading books that are interesting and suitable for children. This research has the implication that collaboration between universities and schools through programs such as the Teaching Campus can be an effective solution in overcoming the problem of children's interest in reading.